The Minimal Geometric Deformation Approach: A Brief Introduction - J. Ovalle; R. Casadio; A. Sotomayor (Advances in High Energy Physics)
We review the basic elements of the Minimal Geometric Deformation approach in detail. This method has been successfully used to generate brane-world configurations from general relativistic perfect fluid solutions.